The Influence Of Brand Image And Celebrity Endorsers On Purchase Intention Of Somethinc Skincare Products Via Instagram Social Media: The Influence Of Brand Image And Celebrity Endorser On Purchase Intention Of Something Skincare Products Through Instagram Social Media - Kholishoh, Mawadlatul; Farida, Lailatul (JURNAL EKBIS, 2023)
The aim of this research is to measure and test the influence of brand image and celebrity endorsers on purchase intention. The research method uses a quantitative approach.The samples used were 120 samples taken using accidental sampling technique. Data collected through distributing online questionnaires to UIN Malang students. Data were analyzed using multiple linear regression with the help of SPSS 16.0 statistical software. The research results show that brand image has a partial effect on purchase intention, celebrity endorsers have a partial effect on purchase intention and brand image and celebrity endorsers together have a significant effect on purchase intention for Somethinc skincare products at the State Islamic University of Malang.